Evaluation of a school-based health education program on hepatitis B virus infection prevention practice in rural South-Western, Nigeria - Titilayo Olaoye; Blessing Osie-Efietie; Ololade O. Ogunsanmi; Adebayo M. Mustapha; Ifeoluwapo Asekun-Olarinmoye; Nnodimele Onuigbo Atulomah (BMC, 2024)
Abstract Background Hepatitis B virus (HBV) infection prevention is most effective early in childhood with vaccination programme. However, where this is missed, primary prevention modes of intervention become an alternative recommendation to be considered before the occurrence of risk exposure to the virus. This study sought to evaluate outcomes of a theory-based HBV infection prevention educational intervention among students from four selected secondary schools in Ogun state, Nigeria. Methodology A quasi-experimental design enrolling 256 consenting secondary school students from four schools in Ogun state randomized into three intervention schools consisting teacher-instructed (E1), peer-directed (E2) and combination of the two (E3) respectively with a control group ( C) was implemented. The theory-based educational intervention was for six weeks with follow-up period of 8 weeks. A 66-item validated instrument was used to collect data at three reference points and response items for variables in the study were transformed into weighted-aggregate scores of mean and standard deviation of HBV infection prevention practice of participants. Statistical analysis of ANOVA, paired-sample t-test and Cohen's D Effect Size (ES) was used to quantify the changes produced by the intervention on the outcome variable at 5% level of significance. Results At baseline, there was no significant difference (p > 0.05) in the mean HBV infection prevention practice scores between the four groups E1 (17.21 ± 3.03), E2 (15.57 ± 1.90), E3 (17.90 ± 3.10), and C (15.20 ± 2.44). However, at 14th week follow up, there was observed significant differences in mean scores of HBV infection prevention practices between all four groups E1 (23.09 ± 2.4), E2 (22.6 ± 3.6), E3 (23.82 ± 2.3), and C (15.25 ± 2.4). Paired-sample t-test conducted demonstrated significant differences between baseline and 14th week follow up for E1 (17.21 ± 3.07 and 23.18 ± 2.9; p = 0.001), E2(15.57 ± 1.90 and 23.53 ± 3.12; p = 0.001), E3(17.90 ± 3.10 and 25.1 ± 2.6; p < 0.001), but not for C (15.20 ± 2.44 and 15.25 ± 2.4; p = 0.92), with most significant impact (ES(95%CI) on HBV infection prevention practices observed for E2(3.106 95%CI: [2.66 to 3.55; p = 0.001]). Importantly, the participants in E2 showed more improvement in prevention practices than their counterparts from E1, E3, and control. Therefore, the intervention demonstrated proof-of-concept in facilitating behavior modification expected. Peer education can be utilized as a strategy to promote Hepatitis B infection prevention practices among adolescents.